Method for preparing negative electrode material of C-iron chlorosulfide composite lithium ion battery by taking copper slag as raw material

The preparation of a C@ferric chlorosulfide composite lithium-ion battery negative electrode material from copper slag addresses the limitations of traditional materials by achieving high capacity and efficiency while mitigating environmental impact.

CN119118205APending Publication Date: 2024-12-13HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410904681.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-07
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials face issues of high cost, low theoretical specific capacity, high toxicity, and environmental harm due to the use of precious metals and toxic substances like lead and arsenic, while materials like BiOCl and Ge have limitations in lithium storage and availability.

Method used

A method is developed to prepare a C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as a raw material, involving a series of chemical treatments and reactions to create a composite with improved lithium storage capacity and conductivity, including mixing copper slag with sodium sulfide or thioacetamide at high pressure and temperature.

Benefits of technology

The method results in a composite material with a first cycle discharge specific capacity of 1480.5 mAh/g and a coulomb efficiency of 76.11%, reducing environmental harm and resource scarcity by utilizing copper slag, and enhancing battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a method for preparing a C-coated iron chlorosulfide composite lithium ion battery negative electrode material by taking copper slag as a raw material. The preparation method comprises the following steps: by taking copper slag as a raw material, removing impurities by using nitric acid, mixing the impurity-removed product with a certain amount of charcoal, sintering at high temperature in an inert atmosphere, acidizing the obtained product by using hydrochloric acid, controlling the pH value of the acidized solution by using ammonia water, and collecting the acidized product to obtain turbid liquid of C and FeCl3; adding a certain amount of a surfactant into the turbid liquid, adding a sodium sulfide or thioacetamide solution according to a certain proportion, stirring, uniformly mixing, transferring into a high-pressure kettle, heating, keeping the temperature for a period of time, and filtering, washing, drying and other operations on the product to obtain the sodium sulfide / thioacetamide composite material. The copper slag serves as the raw material, and the C-iron chlorosulfide composite lithium ion battery negative electrode material is obtained. The C-iron chlorosulfide composite lithium ion battery negative electrode material prepared by using the copper slag as the raw material and prepared by the method disclosed by the invention is in a sphere-like morphology, the first-circle discharge specific capacity reaches 1480.5 mAh / g under the current density of 0.2 A / g, and the first-circle coulombic efficiency reaches up to 76.11%. The method disclosed by the invention is environment-friendly, low in cost and relatively good in repeatability, and the obtained C-iron chlorosulfide composite lithium ion battery negative electrode material taking the copper slag as the raw material reduces the harmfulness of the copper slag to the environment and a human body, realizes waste utilization and is beneficial to environmental protection. And the problems of small resource storage amount, high price, low theoretical specific capacity and the like of the traditional alloy lithium ion battery negative electrode material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically provides a method for preparing a C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as a raw material. Background Art

[0002] Mineral resources are a type of natural resources. Due to the existence form and geographical distribution of most mineral resources, they cannot be used directly. They need the participation of human behavior, such as mining, transportation, refining, processing, etc., to serve production and life. However, in the process of resource development and utilization, slag will inevitably be produced. Some slag contains toxic substances, such as lead, mercury, arsenic, etc., which are extremely harmful to the human body. In addition, the accompanying slag waste will occupy land and pollute the soil, atmosphere and water. The benign operation of the natural environment is the premise for the sustainable development and utilization of natural resources. The reuse of waste is very beneficial to environmental protection. Recently, alloy materials have attracted people's interest as negative electrodes for lithium-ion batteries due to their high lithium storage capacity and low reaction potential. Ge can react with lithium at around 0.4V to form LiGe alloy, but since the product after complete lithiation is amorphous, it is difficult to identify whether the product is a 1:1 LiGe alloy; Pb can also undergo a series of alloying reactions with lithium, but since Pb is a heavy metal, it pollutes the environment; As can react with lithium to form Li3As alloy, but As is very toxic and cannot be used in practice. Among them, two-dimensional layered materials, composed of anion sheets and cation layers, have also been the subject of research by the scientific community and the chemical industry. BiOCl is such a candidate material with layered tetragonal crystals: it is composed of [Bi2O2] alternately stacked between two sheets of chloride ions along the c-axis. 2+ The structure is composed of sheets. This structure can provide a fast diffusion path along the ion layer and between the ion layers. In addition, the layered structure can provide a large space for the insertion and extraction of lithium ions. Bi can also form Li3Bi alloy with lithium. However, due to the large atomic mass of Bi, its theoretical specific capacity is low and the content of bismuth in the earth's crust is low (0.5-1.0mmol / kg), which makes it a relatively rare element. Compared with Bi, Fe is the most abundant metal in copper slag. 3+ The ionic radius Compare Small enough to create an open volume within the ion layer so that Li +The S can diffuse faster during the insertion / extraction process. Moreover, S can be used as an active material because it can form Li2S with lithium and undergo a reversible electrochemical reaction. Its reaction potential is high and it has a high specific capacity (1163mAh / g). At the same time, Fe nanoparticles can also improve the conductivity of Li2S. Therefore, by introducing the iron element extracted from copper slag into alloy materials and combining it with sulfur, it can not only alleviate the energy scarcity problem of precious metals and improve the coulombic efficiency and capacity of the battery, but also turn copper slag into treasure, greatly reducing its harm to the environment and human body. Summary of the invention

[0003] The present invention seeks a preparation process for a C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as a raw material to meet the needs of protecting the environment and improving the performance of lithium-ion batteries. As a solution, the present invention provides a preparation method. The method uses a product obtained by treating copper slag and mixes it with sodium sulfide or thioacetamide at high pressure and high temperature. The obtained C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as a raw material has a first efficiency of up to 76.11% at a current density of 0.2 A / g, and the first cycle discharge specific capacity reaches 1480.5 mAh / g.

[0004] 1. A method for preparing C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as raw material, according to the following steps:

[0005] 1. Evenly mix the copper slag and nitric acid, remove the upper jelly-like gel after the reaction is complete, wash the remaining product with anhydrous ethanol and deionized water successively until the pH value is 5-9, the ratio of copper slag to nitric acid is 1g:0.00001L-1g:0.1L, and the concentration of nitric acid is 0.001-16mol / L;

[0006] 2. Grind the product of step 1 and charcoal in a mass ratio of 1:1 to 1:10, transfer the mixture to a tube furnace, heat to 500 to 1200°C under nitrogen, and keep warm for 1 to 10 hours;

[0007] 3. Wash the product of step 2 with anhydrous ethanol and deionized water successively until the pH value is 5-9, filter and dry it, mix it evenly with hydrochloric acid, stir it with a magnetic stirrer at a speed of 50-500r / min for 10-1000min, and the ratio of the dried product to hydrochloric acid is 1g:0.0001L-1g:0.1L, and the concentration of hydrochloric acid is 0.001-12mol / L;

[0008] 4. Adjust the pH value of the product in step 3 to 5-9 with aqueous ammonia to obtain a suspension of C and FeCl3;

[0009] 5. Add a certain amount of surfactant polyethylene glycol 2000 to the suspension of step 4, stir until the surfactant is completely dissolved, then add sodium sulfide or thioacetamide solution, stir with a magnetic stirrer at a speed of 50-500r / min for 10-60min, the amount of polyethylene glycol 2000 added to the suspension is 0.001-100g / L, the concentration of sodium sulfide or thioacetamide solution is 0.0001-5mol / L, and the volume ratio of sodium sulfide or thioacetamide solution to the suspension is 0.1:1-10:1L;

[0010] 6. Transfer the mixed solution in step 5 into an autoclave, heat to 80-250°C, and keep warm for 10-30 hours;

[0011] 7. Wash the product of step 6 with anhydrous ethanol and deionized water successively until the pH value is 5 to 9;

[0012] 8. Put the product obtained in step 7 into a vacuum drying oven and keep it at 50-100° C. for 8-20 hours to obtain the copper slag as the raw material C@ferric chlorosulfide composite lithium-ion battery negative electrode material.

[0013] The preparation method has the advantages of being environmentally friendly, low cost and high repeatability. The obtained C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as raw material not only solves the problems of small resource storage, high price, low theoretical specific capacity and high toxicity of traditional alloy lithium-ion battery negative electrode materials, but also reduces the harm of difficult-to-handle copper slag to the environment and human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a scanning electron microscope photo of the C@ferric chlorosulfide composite lithium-ion battery negative electrode material prepared using copper slag as raw material in Experiment 1;

[0015] Figure 2 This is the first cycle charge and discharge curve of the C@ferric chlorosulfide composite lithium-ion battery negative electrode material prepared in Experiment 1 using copper slag as raw material;

[0016] Figure 3 This is the cycle diagram of the C@ferric chlorosulfide composite lithium-ion battery negative electrode material prepared with copper slag as raw material in Experiment 1 at a current density of 0.2A / g. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0018] Specific implementation method 1: A method for preparing C@ferric chlorosulfide composite lithium ion battery negative electrode material using copper slag as raw material, according to the following steps:

[0019] 1. Evenly mix the copper slag and nitric acid, remove the upper jelly-like gel after the reaction is complete, wash the remaining product with anhydrous ethanol and deionized water successively until the pH value is 5-9, the ratio of copper slag to nitric acid is 1g:0.00001L-1g:0.1L, and the concentration of nitric acid is 0.001-16mol / L;

[0020] 2. Grind the product of step 1 and charcoal in a mass ratio of 1:1 to 1:10, transfer the mixture to a tube furnace, heat to 500 to 1200°C under nitrogen, and keep warm for 1 to 10 hours;

[0021] 3. Wash the product of step 2 with anhydrous ethanol and deionized water successively until the pH value is 5-9, filter and dry it, mix it evenly with hydrochloric acid, stir it with a magnetic stirrer at a speed of 50-500r / min for 10-1000min, and the ratio of the dried product to hydrochloric acid is 1g:0.0001L-1g:0.1L, and the concentration of hydrochloric acid is 0.001-12mol / L;

[0022] 4. Adjust the pH value of the product in step 3 to 5-9 with aqueous ammonia to obtain a suspension of C and FeCl3;

[0023] 5. Add a certain amount of surfactant polyethylene glycol 2000 to the suspension of step 4, stir until the surfactant is completely dissolved, then add sodium sulfide or thioacetamide solution, stir with a magnetic stirrer at a speed of 50-500r / min for 10-60min, the amount of polyethylene glycol 2000 added to the suspension is 0.001-100g / L, the concentration of sodium sulfide or thioacetamide solution is 0.0001-5mol / L, and the volume ratio of sodium sulfide or thioacetamide solution to the suspension is 0.1:1-10:1L;

[0024] 6. Transfer the mixed solution in step 5 into an autoclave, heat to 80-250°C, and keep warm for 10-30 hours;

[0025] 7. Wash the product of step 6 with anhydrous ethanol and deionized water successively until the pH value is 5 to 9;

[0026] 8. Put the product obtained in step 7 into a vacuum drying oven and keep it at 50-100° C. for 8-20 hours to obtain the copper slag as the raw material C@ferric chlorosulfide composite lithium-ion battery negative electrode material.

[0027] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the pH value in step 1 is controlled to be 6-8, the ratio of copper slag to nitric acid is 1g:0.001L-1g:0.01L, and the concentration of nitric acid is 0.01-8mol / L.

[0028] Specific implementation method three: This implementation method is different from specific implementation methods one to two in that the mass ratio of the product to charcoal in step two is controlled at 1:1 to 1:4, the sintering temperature in the tubular furnace is 500 to 800°C, and the insulation time is 3 to 5 hours.

[0029] Specific implementation method four: This implementation method is different from specific implementation methods one to three in that the pH value in step three is controlled at 5 to 7, the speed of the magnetic stirrer is 100 to 300 r / min, the stirring time is 100 to 800 min, the ratio of the dried product to hydrochloric acid is 1 g: 0.001 L to 1 g: 0.01 L, and the concentration of hydrochloric acid is 0.1 to 10 mol / L.

[0030] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the pH value in step 4 is controlled at 5-7.

[0031] Specific embodiment six: This embodiment is different from specific embodiments one to five in that the volume ratio of sodium sulfide or thioacetamide solution to suspension in step five is 0.1:1~5:1L, the amount of polyethylene glycol 2000 added to the suspension is 0.01~5g / L, the speed of the magnetic stirrer is 100~300r / min, and the stirring time is 20~50min.

[0032] Specific implementation method 7: The difference between this implementation method and specific implementation methods 1 to 6 is that the heating temperature in step 6 is 100-200° C. and the insulation time is 10-25 hours.

[0033] Specific implementation method eight: This implementation method is different from specific implementation methods one to seven in that the pH value in step seven is controlled to be 5-7.

[0034] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that the insulation temperature in step 8 is 60-85° C. and the insulation time is 8-15 hours.

[0035] The following experiments were used to verify the effect of the present invention:

[0036] Experiment 1:

[0037] A method for preparing C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as raw material and product performance test:

[0038] 1. Take 10g of copper slag and mix it evenly with 0.1L of 12mol / L nitric acid. After the reaction is complete, remove the upper jelly-like gel and wash the remaining product with anhydrous ethanol and deionized water successively until the pH value is 7;

[0039] 2. Grind 5 g of the product from step 1 with 20 g of charcoal, transfer the mixture to a tube furnace, heat to 900 °C under nitrogen, and keep warm for 3 h.

[0040] 3. Wash the product of step 2 with anhydrous ethanol and deionized water successively until the pH value is 7, filter and dry it, mix it evenly with hydrochloric acid, stir it with a magnetic stirrer at a speed of 300r / min for 720min, and the ratio of the dried product to hydrochloric acid is 1g:0.01L, and the concentration of hydrochloric acid is 12mol / L;

[0041] 4. Adjust the pH value of the product in step 3 to 7 with aqueous ammonia;

[0042] 5. Take 100 ml of the product of step 4, add 1 g of surfactant polyethylene glycol 2000 thereto, stir until the surfactant is completely dissolved, add 20 ml of 1 mol / L thioacetamide solution to the mixed solution, and stir with a magnetic stirrer at a speed of 300 r / min for 20 min;

[0043] 6. Transfer the mixed solution in step 5 into an autoclave, heat to 150°C, and keep warm for 15 hours;

[0044] 7. Wash the product of step 6 with anhydrous ethanol and deionized water successively until the pH value reaches 7;

[0045] 8. The product obtained in step 7 is placed in a vacuum drying oven and kept at 85° C. for 8 hours to obtain copper slag as raw material C@ferric chlorosulfide composite lithium-ion battery negative electrode material.

[0046] Product performance test:

[0047] 1. The C@ferric chlorosulfide composite lithium-ion battery negative electrode material prepared in Experiment 1 with copper slag as raw material was uniformly mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 8:1:1, and solvent N-methylpyrrolidone was added to prepare a slurry, and the slurry was coated on a copper foil to obtain an electrode sheet;

[0048] 2. Place the electrode sheet in a vacuum drying oven and dry it at 90°C for 12 hours. After the electrode sheet is completely dry, punch it into a circular electrode sheet with a diameter of 14 mm.

[0049] 3. The obtained circular electrode sheet was used as the negative electrode, the metal lithium sheet was used as the positive electrode, GradeGF / A was used as the separator, and the electrolyte formula was EC / DMC (1:1)-LiPF6 (1M), and the battery was assembled in a box;

[0050] 4. Use the Blue CT3002A battery test system to perform constant current charge and discharge tests in the voltage range of 0.01 to 3 V. The electrochemical test results show that the first cycle discharge capacity reaches 1480.5 mAh / g at a current density of 0.2 A / g, and the first cycle coulomb efficiency is as high as 76.11%.

[0051] Experiment 2:

[0052] A method for preparing a C@ferric chlorosulfide composite lithium-ion battery negative electrode material using copper slag as a raw material is carried out according to the following steps:

[0053] 1. Take 10g of copper slag and mix it evenly with 0.05L of 10mol / L nitric acid. After the reaction is complete, remove the upper jelly-like gel and wash the remaining product with anhydrous ethanol and deionized water successively until the pH value is 6;

[0054] 2. Grind 3 g of the product from step 1 with 18 g of charcoal, transfer the mixture to a tube furnace, heat to 1200°C, and keep warm for 6 hours;

[0055] 3. Wash the product of step 2 with anhydrous ethanol and deionized water successively until the pH value is 6, filter and dry it, mix it evenly with hydrochloric acid, stir it with a magnetic stirrer at a speed of 500r / min for 1000min, and the ratio of the dried product to hydrochloric acid is 1g:0.05L, and the concentration of hydrochloric acid is 10mol / L;

[0056] 4. Adjust the pH value of the product in step 3 to 6 with aqueous ammonia;

[0057] 5. Take 120 ml of the product of step 4, add 0.75 g of surfactant polyethylene glycol 2000 thereto, stir until the surfactant is completely dissolved, add 10 ml of 3 mol / L thioacetamide solution to the mixed solution, and stir with a magnetic stirrer at a speed of 400 r / min for 30 min;

[0058] 6. Transfer the mixed solution in step 5 into an autoclave, heat to 180°C, and keep warm for 10 hours;

[0059] 7. Wash the product of step 6 with anhydrous ethanol and deionized water successively until the pH value reaches 6;

[0060] 8. The product obtained in step 7 is placed in a vacuum drying oven and kept at 65° C. for 12 h to obtain copper slag as raw material C@ferric chlorosulfide composite lithium-ion battery negative electrode material.

Claims

1. A method for preparing C@ferric chlorosulfide composite lithium ion battery negative electrode material using copper slag as raw material, according to the following steps:

1. Evenly mix the copper slag and nitric acid, remove the upper jelly-like gel after the reaction is complete, wash the remaining product with anhydrous ethanol and deionized water successively until the pH value is 5-9, the ratio of copper slag to nitric acid is 1g:0.00001L-1g:0.1L, and the concentration of nitric acid is 0.001-16mol / L; 2. Grind the product of step 1 and charcoal in a mass ratio of 1:1 to 1:10, transfer the mixture to a tube furnace, heat to 500 to 1200°C under nitrogen, and keep warm for 1 to 10 hours; 3. Wash the product of step 2 with anhydrous ethanol and deionized water successively until the pH value is 5-9, filter and dry it, mix it evenly with hydrochloric acid, stir it with a magnetic stirrer at a speed of 50-500r / min for 10-1000min, and the ratio of the dried product to hydrochloric acid is 1g:0.0001L~1g: 0.1L, the concentration of hydrochloric acid is 0.001~12mol / L; 4. Adjust the pH value of the product in step 3 to 5-9 with aqueous ammonia to obtain a suspension of C and FeCl3; 5. Add a certain amount of surfactant polyethylene glycol 2000 to the suspension of step 4, stir until the surfactant is completely dissolved, then add sodium sulfide or thioacetamide solution, stir with a magnetic stirrer at a speed of 50-500r / min for 10-60min, the amount of polyethylene glycol 2000 added to the suspension is 0.001-100g / L, the concentration of sodium sulfide or thioacetamide solution is 0.0001-5mol / L, and the volume ratio of sodium sulfide or thioacetamide solution to the suspension is 0.1:1-10:1L; 6. Transfer the mixed solution in step 5 into an autoclave, heat to 80-250°C, and keep warm for 10-30 hours; 7. Wash the product of step 6 with anhydrous ethanol and deionized water successively until the pH value is 5 to 9; 8. Put the product obtained in step 7 into a vacuum drying oven and keep it at 50-100° C. for 8-20 hours to obtain the copper slag as the raw material C@ferric chlorosulfide composite lithium-ion battery negative electrode material.